Guided exercises with or without joint mobilization or no treatment in patients with subacromial pain syndrome: A clinical trial - Anna Eliason; Marita Harringe; Björn Engström; Suzanne Werner (Journal of Rehabilitation Medicine, 2021)

(untitled)
Background: Graded resistance training is the recommended treatment for patients with subacromial pain syndrome. It is debated whether adding joint mobilization will improve the outcome. The aim of this study was to evaluate the clinical outcome of guided exercises with or without joint mobilization, compared with controls who did not receive any treatment. Methods: A 3-armed controlled trial in a primary care setting. A total of 120 patients, with clinically diagnosed subacromial pain syndrome, were randomized into guided exercise groups with and without additional joint mobilization, and a control group that did not receive any treatment. Data were analysed at baseline, 6 weeks, 12 weeks and 6 months. Primary outcome was the Constant-Murley score, and secondary outcomes were pain and active range of motion. Results: Shoulder function improved in all groups, as measured with the Constant-Murley score. At 12 weeks and 6 months the exercise groups improved significantly compared with the control group (p ≤ 0.05). Add-on joint mobilization resulted in decreased pain in active range of motion at 6 and 12 weeks compared with guided exercise or no treatment (p ≤ 0.05). Range of motion increased over time in all 3 groups. Conclusion: In patients with subacromial pain syndrome guided exercises improved shoulder function compared with no treatment. Add-on joint mobilization decreased pain in the short-term compared with exercise alone or no treatment.